Case Report: Developmental-like skeletal deformities and transient osteosclerosis as rare presentations of primary hyperparathyroidism - Deng, Peijun; Wang, Qin; Huang, Miaoxian; Wu, Haiying; Huang, Jianwen; Li, Jie; Gao, Xiaosheng; Zhou, Mi; Yang, Yunfa; Liang, Junbo (Frontiers in Endocrinology, 2026)
BackgroundSkeletal disorders in primary hyperparathyroidism (PHPT) classically manifest with osteoporosis or brown tumors. While skeletal deformities are documented in resource-limited areas, coxa vara combined with genu valgum remains unreported.Case PresentationA 14-year-old Tibetan female from rural China presented with progressive bilateral coxa vara (left: 102.45°, right: 109.10°) and genu valgus (left: 24.20°, right: 18.80°). Staged osteotomies for lower limb deformities were planned. After the stage 1 osteotomy, severe hypercalcemia (peak: 3.79 mmol/L; reference: 2.11–2.52 mmol/L) and elevated PTH (995 pg/mL; reference: 15–65 pg/mL) emerged, leading to Single-photon emission computed tomography (SPECT) confirmed diagnosis of a left inferior parathyroid adenoma. Following the multidisciplinary team (MDT) recommendation, parathyroidectomy (PTX) achieved a biochemical cure, though postoperative hypocalcemia (nadir: 1.62 mmol/L; reference: 2.11–2.52 mmol/L) required aggressive calcium and calcitriol supplementation. After metabolic stabilization, the stage 2 osteotomy was performed. Notably, multifocal osteosclerotic regions around the knees emerged during the X-ray follow-up, resolving within 1 year with rigorous perioperative calcium and vitamin D management. One-year follow-up confirmed complete bony union, functional recovery, and deformity correction.ConclusionThis case highlights two key points: first, PHPT can masquerade as developmental skeletal deformity in adolescents, mandating a high index of suspicion and biochemical screening. Second, we describe a novel, self-resolving phenomenon of transient postoperative osteosclerosis, likely representing a reparative bone response following biochemical cure. Successful orthopedic correction before full metabolic normalization underscores the feasibility of staged management with meticulous perioperative care. These observations expand the phenotypic spectrum of pediatric PHPT.